Implementation of Development Journalism in the Reformation Era (The Case Study of Behavioral Change Journalism Fellowship Program from the Press Council during the Covid-19 Pandemic) - Susilastuti Dwi Nugraha Jati (Journal of International Conference Proceedings, 2021)
The reform era marked by the fall of the New Order government bring changes in all aspects, including the development journalism in Indonesia. The development journalism has ever become a prima donna and it has submerged along with the emergence of journalism that positions journalists as the guardians of the public interest, such as anticorruption journalism, pro-gender journalism, budgeting, election journalism, children's journalism and data journalism. On the other hand, the development journalism has begun to be rarely discussed. One of the reasons for this journalism seems to place journalists as pawns for the interests of the government. In the middle of Covid-19 pandemic era, however, the development journalism in a different version from the New Order era is used again. The government through the behavioral change journalism fellowship program places journalists as an agency to encourage people's behavior change when encountering the Covid-19 pandemic. The program is carried out by the Indonesian Press Council in collaboration with the Covid-19 Task Force and it involves 3030 journalists who have received recommendations from the constituent members of the Indonesian Press Council from various media platforms that have been carried out since 2020. The involvement of the journalists in this behavioral change program is the implementation of the development journalism that positions journalists as an agency. This study shows that the liveliness of journalists as an agency in responding to the structures is carried out to find the momentum of change to various issues in the society. This liveliness is intended that there is no monopoly of information from the power structure and it provides various opportunities for the public to obtain favourable information and avoid monopoly of information from the structure. The activities of this agency can no longer place the journalists with their activities into resonance, an irritation for the government in carrying out its programs. People's behavioral change is required in the middle of Covid-19 pandemic era. Efforts to encourage behavioral change cannot be merely conducted by the government. Journalists are one of the agents of change and they are cooperating with the government. This is in line with the implementation of the development journalism which places journalists as the government partners to encourage the government programs. The agency's involvement in its relationship with the power structure related to the COVID-19 pandemic does not bring down the ruling government but they will help explain to the public the problems the government is facing regarding the Covid-19 pandemic.